The Relationship of Nurse Response Time with Patient Satisfaction BPJS at the Emergency Installation of the Bayukarta Hospital Karawang - Musa Buwana Raya; Monica Ginting; Reynaldi Tresnajaya (Indonesian Journal of Health Research and Development, 2024)
One of the quality indicators in measuring the performance of the Emergency Department (IGD) is the response time of patient services in the ER, namely the speed of patient treatment which is calculated from the time the patient arrives until he receives treatment in less than 5 minutes (Decree of the Minister of Health of the Republic of Indonesia No: 856/Menkes/SK /IX/2009). Response Time of nurses in handling emergencies quickly and appropriately will increase satisfaction for patients and families of BPJS Health patients. The aim of this research is to determine the relationship between nurse response time and BPJS Health patient satisfaction in the emergency room at Bayukarta Karawang Hospital. This research uses descriptive analytical correlation research with a cross sectional design. The instruments used in this research used a patient satisfaction questionnaire sheet and a response time observation sheet. The sample in this study was 81 respondents from BPJS Health patients, using accidental sampling technique. Results. Statistical tests use the Chi square test. The results of the analysis using the Chi square statistical test obtained the Asymp value. Sig. (2 tailed) of 0.00. Because the value of Asymp. Sig. (2 tailed) < α (α = 0.05), The conclusion of this research is that there is a relationship between nurse response time and BPJS Health patient satisfaction in the installation at the Bayukarta Karawang Hospital ER. It is hoped that this research can be used to develop further research into researchers who are interested in developing research in the field of emergency nursing, especially regarding nurse responsiveness and patient satisfaction.